Reference Intervals (RIs) of the Bone Turnover Markers (BTMs) in Children and Adolescents: A Proposal for Effective Use - Vincenzo Brescia; Roberto Lovero; Antonietta Fontana; Roberta Zerlotin; Silvia Concetta Colucci; Maria Grano; Angela Pia Cazzolla; Francesca Di Serio; Vito Crincoli; Maria Felicia Faienza (Biomedicines)
Background/Objectives: Bone turnover markers (BTMs) can provide information on the bone growth of apparently healthy children and adolescents or useful results in the diagnosis and monitoring of the disease condition, comparing them with appropriate reference intervals (RIs). The aim of this study was to establish the RI for the BTM [specific bone alkaline phosphatase (BALP), carboxy-terminal cross-linked collagen type I telopeptide (CTX), N-terminal propeptide pro-collagen type I (PINP), osteocalcin (OC), resistant to acid tartrate phosphatase isoform 5b (TRAcP-5b)] on serum samples from children and adolescents. Method: 202 samples from children and adolescents (ages 1–18 years) (51.48% male), considered apparently healthy. The biomarker was analyzed on automatic immunometric equipment (TGSTA Technogenetics) and the IDS-iSYS automated system kits The RI of the studied parameters was calculated according to CLSI Guideline C28-A3 with stratification by age and sex. Evaluation of the distribution of values and the meaning of the biomarker concentrations were used to calculate general and specific RI for an age group. Results: BTM concentrations vary with pubertal growth. The pattern of change differs for each bone marker. General and age-specific RI were calculated: 1–14 years, 15–18 years for BALP and CTX; 1–13 years, 14–18 years for Oc and PINP and 1–12 years, 13–18 years for TRAcP. Discussion and Conclusions: Concentrations for biomarker studied vary with age and gender. The proof of concentrations with insignificant changes until puberty led to identification of two groups of RI relating to the covariables (age and sex) for each biomarker.